First-Time Mothers' Invisible Presence Using Social Networking Sites. Issue 6 (November 2022) - Elliott, Gail M. C.; Letvak, Susan; Côté-Arsenault, Denise; Wallace, Debra C.; Smith, Julia Mendez
Abstract: Purpose: To describe first-time mothers' experiences with online social networking sites in the early postpartum period, explore how mothers use them to gain support, and to evaluate how their use can aid or hinder maternal role transition. Study Design: Qualitative descriptive study. Methods: This qualitative descriptive study, using convenience and snowball sampling, first-time mothers in the early postpartum period were recruited through social media. Semistructured interviews were conducted virtually where mothers were asked to describe their experiences with online social networking. Thematic analysis methods were used to develop themes from participant interviews. Results: Twelve first-time mothers ranging from 4 to 12 weeks postpartum participated in the study. Thematic analysis revealed four themes: 1) Habits of first-time mom using social networking sites, 2) New purpose online, 3) Taking it to the moms, and 4) Impact on motherhood. Clinical Implications: Maternal child nurses have opportunities to further customize support for first-time mothers online. Awareness of habits, trends, implications of early mothering during COVID-19, and the role social networking sites can play in supporting mothers in the early postpartum period offers new ways for nurses to support and empower the motherhood collective. Abstract : New mothers are frequent users of social media sites. In this study, 21 first-time new mothers were interviewed about how they used social media during the first months postpartum. Mothers reported they logged on multiple times a day, often during the night and adjusting to infant feeding and napping schedules. They believed the sites offered a safe space for mothers to have access to information and support while maintaining some degree of anonymity. Nurse familiarity with existing online social media sites can be beneficial in guiding new mothers to reputable resources.